Light limitation and coral mortality in urbanised reef communities due to sea-level rise - Law, Mei Ting; Huang, Danwei (Climate change ecology, 2023)
Sea-level rise (SLR) is expected to elevate the depth of seawater above shallow coral reefs, reducing light availability to the benthic environment, and impacting the survival and growth of corals especially on turbid reefs. However, the extent of impact at the deepest reef zones remains unknown. Coral growth could continue to keep pace above light thresholds as sea level rises, but mortality due to light limitation could vary between localities and local conditions. Here, we examine possible outcomes of corals inhabiting Singapore's turbid reefs in the years 2050 and 2100 by characterising their depth distributions and predicting potential mortality rates based on SLR projections. Our results reveal that in 2050, under both RCP4.5 and RCP8.5 sea level projections, up to 6.24% of colonies could face mortality if their growth is not considered. In 2100, up to 7.68% mortality under RCP4.5 and up to 10.7% mortality under RCP8.5 are predicted. When coral linear extension is considered, in 2050, under both RCP4.5 and RCP8.5 sea level projections, up to 1.03% of colonies could face mortality. In 2100, up to 0.87% mortality under RCP4.5 and up to 1.84% mortality under RCP8.5 are predicted. Species-specific losses could amount to 20% of colonies primarily at the deepest zones. The most vulnerable species exhibit a depth distribution with most colonies situated at the deeper parts of their depth ranges. Our findings suggest that sea-level rise may potentially result in the loss of coral cover for some species, but overall mortality could be low. [Display omitted]